Immunological Parameters and Laying Performance of Naked Neck and Normally Feathered Genotypes of Chicken under Winter Conditions of Egypt - El-Safty, S.A.; Ali, U.M.; Fathi, M.M. (International Journal of Poultry Science, 2006)
The study was undertaken to evaluate and measure some immunological traits and laying performance for two genotypes (heterozygous naked neck and normally feathered) of chicken under low ambient temperature. The Nana hens had heavier body weight and slightly higher body temperature as compared to nana one. According to H/L ratio and leucocyte percentages, it could be seen that the nana birds were more stressed than Nana counterparts. The results of PHA-P assay showed that the Nana hens had a significantly greater dermal swelling compared to normally feathered ones. Additionally, the normal plumage hens had a higher mortality and culling rate than heterozygous naked neck hens. Concerning egg production and eggshell quality measurements, the nana hens had a better performance than Nana ones. In naked neck hens, there was a positive relationship among egg mass, egg number and cell mediated response occurs at 48 and 72h post-injection. While, in normally feathered genotype, there was a highly positive correlation between egg weight and cell-mediated response at 72h post-injection.